Step
*
1
1
of Lemma
rsqrt-rmul
1. x : {x:ℝ| r0 ≤ x} 
2. y : {x:ℝ| r0 ≤ x} 
⊢ ((rsqrt(x) * rsqrt(y)) * rsqrt(x) * rsqrt(y)) = (x * y)
BY
{ (nRNorm 0 THEN (RWO "rsqrt_squared" 0 THENA Auto)) }
1
1. x : {x:ℝ| r0 ≤ x} 
2. y : {x:ℝ| r0 ≤ x} 
⊢ (rsqrt(x) * rsqrt(x) * y) = (x * y)
Latex:
Latex:
1.  x  :  \{x:\mBbbR{}|  r0  \mleq{}  x\} 
2.  y  :  \{x:\mBbbR{}|  r0  \mleq{}  x\} 
\mvdash{}  ((rsqrt(x)  *  rsqrt(y))  *  rsqrt(x)  *  rsqrt(y))  =  (x  *  y)
By
Latex:
(nRNorm  0  THEN  (RWO  "rsqrt\_squared"  0  THENA  Auto))
Home
Index